Giới thiệu lý thuyết tương hợp và khả năng ứng dụng trong một số bài toán xác lập thị trường ở Việt Nam - Trần Thị Tuấn, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
Matching theory is an important branch of game theory that helps to solve problems of market design in which price does not work as in traditional markets. This article briefly summarizes the matching theory according to main aspects such as two-side matching problems: One-to-one, one-to-many, many-to-many problems; or one-sided matching as resource allocation problems. In spite of the simplicity of Deferred Acceptance Algorithm (DAA), it is also an effective tool to find a stable matching for these design market problems. Matching theory has many significantly practical applications in numerous countries around the world such as school choice problems, kidney exchange systems, labor market matching, resource allocation problems, and further applications in market design. In the context of Vietnam, similar market design problems have also arisen and therefore, there are potential applications of matching theory in Vietnam and will certainly yield meaningful results